Temporal trends in the inclusion of patient-reported outcomes in heart failure randomized trials published in high-impact medical journals: a systematic bibliometric review. (14th October 2021) - Eliya, Y; Averbuch, T; Le, N; Xie, F; Thabane, L; Mamas, M; Van Spall, H
Abstract: Background: Patient reported outcomes (PROs) are important measures of health, particularly in symptomatic conditions such as heart failure (HF), and regulatory agencies have encouraged their collection in randomized controlled trials (RCTs). Purpose: To assess temporal trends in the inclusion of patient-reported outcomes (PROs) in heart failure (HF) randomized controlled trials (RCTs) published in high-impact medical journals, explore trial characteristics associated with inclusion of PROs, and describe the quality of PRO reporting in HF RCTs. Methods: We searched MEDLINE, EMBASE and CINAHL for studies published between January 1, 2000 and July 17, 2020. We included RCTs published in journals with impact factor ≥10. We assessed temporal trends using the Jonckheere-Terpstra test and conducted multivariable logistic regression analysis to explore trial characteristics independently associated with inclusion of PROs. We assessed the quality of PRO reporting using the Consolidated Standards for Trial Reporting PRO extension statement. Results: We identified 12, 342 articles, of which 417 RCTs met inclusion criteria. PROs were included in 224 RCTs (53.7%, 95% confidence interval [CI]: 48.8%-58.6%), of which 44 (19.6%) reported PRO as primary or co-primary endpoint. The proportion of RCTs with PROs increased significantly between 2000–2003 (37.4%) and 2016–2020 (65.1%) (p<0.001). PROs had higher odds of inclusion in RCTs that were multicenter (odds ratio [OR]: 1.95; 95% CI: 1.05–3.64; p=0.036); medium-sized (n=51–250) (OR: 2.29; 95% CI: 1.24–4.23; p=0.008); coordinated in in Central and South America (OR: 6.79; 95% CI: 1.34–34.36; p=0.021); and assessed health services (OR: 4.21; 1.97–8.98; p<0.001), device / surgical (OR: 6.24; 95% CI 3.05–12.80; p<0.001), or exercise and rehabilitation interventions (OR: 3.98; 95% CI 1.59–9.97; p=0.003). A majority (54.9%) of the 224 RCTs reported four or less of the eleven CONSORT-PRO items. The median number of CONSORT-PRO items reported was 4 (interquartile range [IQR] 3–6 items per trial), with improved reporting in trials with PRO as primary or co-primary endpoint. Conclusions: PROs are included in in just over half of HF RCTs, with an increased reporting of PROs between 2000 and 2020. Large, pharmacotherapy trials conducted in North America and Europe were less likely to include PROs. The quality of PRO reporting in HF RCTs was modest, with trials most often reporting four of eleven CONSORT-PRO items. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Canadian Institutes of Health Research